2021
DOI: 10.1111/bjd.20489
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia barbae severity score: a novel scoring system to estimate the extent of beard loss and success of treatment

Abstract: healthy textured hair, as identified by a literature review [3][4][5][6] (Table 1).Our search for 'natural hair dermatologist' yielded only six videos by four dermatologists. The average number of followers was 335 152 across all 79 unique authors represented in our sample, reflecting the engagement power of YouTube and its potential to reach a large audience. Our results showed that 46 of 90 influencer videos discussed some combination of specific recommendations for textured hair (protective styling, wearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The ALBAS tool considers effect modifiers such as grooming preferences, pre-existing scars, atrichia and shows high inter-rater confluence scores. The ALBAS tool shows that the neck region was most affected, having a median score of 6.8/10 followed by the left and right beard regions (combined median score of 5.2/10) [40]. This finding corroborates with findings in other studies that showed the neck and beard sides to be the most visibly affected by BAA [7,30,36].…”
Section: Discussionsupporting
confidence: 88%
“…The ALBAS tool considers effect modifiers such as grooming preferences, pre-existing scars, atrichia and shows high inter-rater confluence scores. The ALBAS tool shows that the neck region was most affected, having a median score of 6.8/10 followed by the left and right beard regions (combined median score of 5.2/10) [40]. This finding corroborates with findings in other studies that showed the neck and beard sides to be the most visibly affected by BAA [7,30,36].…”
Section: Discussionsupporting
confidence: 88%
“…Despite widespread use, such terms are only vaguely descriptive. Several tools have been created to assist with assessing scalp AA severity in clinical practice and clinical trials [23][24][25][26][27][28][29][30][31] .…”
Section: Severity Stagingmentioning
confidence: 99%